Comparative Study of Specific Absorption Rate Analysis of Selected Cell Phone Brands around the Head in Kathmandu Valley - Neupane, Bijay Raj; Khadka, Narendra; Sedai, Pukar; Amgain, Suman; Koirala, Maha Prasad; Paudel, Purushottam; Baniya, Smriti; Budhathoki, Khagendra; Baniya, Hom Bahadur (Perspectives on Higher Education, 2025)
The electric fields emitted by commonly used cell phones of various brands were measured at different conditions by using ‘Tenmars, TM196’. The specific absorption rate (SAR) around the head was calculated using ICNIRP guidelines. SAR value is crucial to minimize radiation exposure. It was observed that the maximum regular exposure to radiation occurred in dialing, ringing, and receiving modes. Among the studied smartphones, four out of five devices from Huawei and Xiaomi were found to have more SAR values in the range of 0.009 to 0.012 W/kg at the idle condition and 0.016 to 0.021 W/kg at dialing, ringing, and receiving cases whereas four out of five devices from Samsung were found to have low SAR values in the range of 0.004 to 0.009 W/kg at the idle condition and 0.008 to 0.016 W/kg in dialing, ringing and receiving cases. Non-smart phones emitted negligible radiation in idle conditions with SAR values in the range of 9.10×10-5 to 1.64×10-4 W/kg, but in dialing, ringing, and receiving modes, these phones have higher SAR values of 0.016 to 0.022 W/kg. It is hoped that the SAR values will be useful to mobile users in selecting the appropriate brand of cell phone to minimize the long-term health implications due to radiofrequency exposure.